KUALITAS PENGUNGKAPAN CSR PADA PERUSAHAAN LQ45 DAN FAKTOR YANG MEMPENGARUHINYA - Solikhah, Badingatus; Kuswoyo, Adistya (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2019)
The purpose of this study is to examine the effect of board commissioners meeting frequency, board directors gender diversity, institutional ownership, managerial ownership, industrial sensitivity, and slack resources on CSR disclosure. The population of this study is LQ45 companies listed on the Indonesia Stock Exchange. The sample selection used purposive sampling method, thus obtained 77 unit of analysis. This study used multiple regression analysis. The results showed that frequency of board commissioners meeting and indsutry sensitivity has positive significant effect on CSR disclosure. Meanwhile, boar director gender diversity, innstitutional ownership, managerial ownership, and slack resources do not affect the CSR disclosure.